Provenance Variation in Seed Biometry, Germination and Seedling Traits in Azadirachta indica A. Juss (Neem) - Mayavel, A.; Krishnan, S.; Warrier, Rekha R.; Lingeshwaran, P. K.; Soosai, Raj J.; Sivakumar, V. (International Journal of Bio-resource and Stress Management, 2023)
The present investigationon evaluation of provenance variations in seed morphometric, germination and seedling growth attributes of Neem was conducted at Division of Genetics and Tree Improvement at Institute of Forest Genetics and Tree Breeding, Coimbatore, Tamil Nadu, India with an aim to study the variation in different provenances of Azadirachta indicafor seed morphometry, germination and seedling traits,to identify superior provenances of Azadirachta indica to produce quality planting stocks, during monsoon of 2021 and 2022. Extensive surveys were conducted in 6 different agro-climatic zones in Tamil Nadu and selected 30 Candidate Plus Trees (CPT’s) based on growth superiority and higher fruit yield. The significant differences were recorded on seed length (cm), seed width (cm), seed perimeter (cm), seed area, and 100 seed kernel weight (g), germination percentage, mean daily germination, germination value, germination time, peak value, time spread of germination and germination index and seedling characters such as shoot length, root length, color diameter, leaf numbers, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, shoot and root vigorous index among the provenances and seed lots. Southern Zone and Rainfall Zone provenances recorded higher values on seed length and breadth, seed weight and seedling parameters and lower values of seed parameters were observed in the Western Zone and seedling parameters in North Eastern Zone. Seed length, seed area, seed perimeter and germination percentage had a significant strong positive correlation with the shoot vigour index. Southern Zone and Rainfall Zone provenances can be recommended for establishing large-scale plantation in the Tree Outside Forest (ToF).